EFFECT OF MUCUNA COCHINCHINENSIS EXTRACTS ON EFFLUX PUMP IN FUNGAL STRAINS - K., NATARAJAN; N., KUMARESH JAWAHAR (International Journal of Current Pharmaceutical Research, 2020)
Objective: To study the efflux pump inhibition activity of Mucunacochinchinensis extracts Methods: Sensitivity assay was performed by Kirby Bauer technique. Effluxing ability of microbe was done by accretion, accumulation and efflux pump assays. Results: Resistant fungal strains were subjected to efflux ability studies. Maximum effluxing ability was determined from the experimental data and it was found to be 105 min and 75 min by Candida albicans for methanolic extract of M. cochinchinenesis (MMC) and ethanolic extract of M. cochinchinensis (EMC) respectively and 45 min and 105 min by Aspergillus niger for MMC and EMC respectively. Profound synergistic effect of inhibition was observed with combined MMC and standard Clotrimoxazole when compared to the standard alone; against C. albicansindicates the modulating efficacy of MMC. Conclusion: M. cochinchinensis extracts showed efflux pump modulating activity.